The geochemistry and petrogenesis of Carnley Volcano, Auckland Islands, SW Pacific. Issue 4 (2nd October 2018) - Gamble, John A.; Adams, Chris J.; Morris, Paul A.; Wysoczanski, Richard J.; Handler, Monica; Timm, Christian
ABSTRACT: Intraplate volcanism across Zealandia, South Eastern Australia, the Ross Sea Embayment and Marie Byrd Land in Antarctica define a magmatic province characterised by basalts with elevated 206 Pb/ 204 Pb (18.9–22.5), 87 Sr/ 86 Sr = ∼0.7035, Light Rare Earth enrichment [(Ce/Yb) n  > 10], and convex-up mantle normalised incompatible multi-element patterns, peaking at Nb-Ta, with negative K and Pb anomalies. Trace element abundances and ratios (e.g. Zr/Nb, Y/Zr) resemble Ocean Island Basalts (OIB), distinct from Mid-Ocean Ridge Basalt (MORB), suggesting derivation from OIB-like reservoirs. Our preferred scenario envisages partial melting across the garnet-spinel stability fields involving asthenospheric and lithospheric mantle components. Melts accumulate in a column where the deep (asthenospheric) source is PM and the shallower source a melange of PM and subcontinental lithospheric mantle (DMM+1) enriched by carbonatite. Evolution of primary and near-primary magmas is controlled by olivine + clinopyroxene fractionation. Trachybasalts, trachytes and rhyolites show isotopic evidence for interaction with continental crust.